Vuk’s Lyrical Folk Poems in the "Serbian Dictionary" - Jelić, Marijan J. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
The paper investigates how and to what extent lyrical folk poems served Vuk Karadžić as material for the Serbian dictionary (Srpski rječnik – SR). The research shows that almost all words from lyrical folk poems (from the collection of Serbian lyrical folk poems, book one) were found as lemmata in SR (about 95% of all words from the collection), and that 1,173 lexemes also include verses from lyrical folk poems. The largest group of words that is missing in SR are proper nouns (most often personal names). The numerous lexicon that was less frequently used, which is less known, of foreign origin, regionally marked and which is used only or mainly in the poems, was approached in such a way that verses were given as an example (one or more), so that the word was presented and understandable as much to the future reader of the SR, but also to the reader of lyrical folk poems.Lyrical folk poems and SR are closely related—lyrical (and epic) poems served Vuk to create the SR, but it can also be said that there is an inverse relationship—that the SR served the collections of lyrical (and epic) poems by presenting and explaining a large number of words that are less known and infrequently used. This procedure was not only aimed at presenting the lexicon that should be the basis of the future standard language, but also at presenting the lexicon that may not be, but being part of the main sources of the future standard language, it was necessary to include it as much as possible in SR and present it as precise as possible (to the future readers of Vuk’s poem collections).
Keywords: lexicon; lyrical folk poems; Serbian Dictionary; verses; examples; variants; frequency